Pemanfaatan Media Digital Interaktif dalam Pembelajaran Biologi untuk Meningkatkan Motivasi Siswa - Satria Bramantyo Putra; Surya Atmadja Wicaksono; Rakha Wiratama (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
The integration of interactive digital media in biology learning has become an innovative approach to enhancing student motivation. This study aims to investigate the impact of interactive digital media on students' engagement and learning outcomes in biology. A quantitative research method was employed, utilizing a quasi-experimental design with pre-test and post-test assessments. The participants consisted of high school students divided into experimental and control groups. The experimental group used interactive digital media, while the control group followed traditional learning methods. The findings indicate that students who utilized interactive digital media demonstrated a significant increase in motivation and academic performance compared to those in the control group. The study highlights the effectiveness of digital media in fostering an engaging learning environment, suggesting its broader application in science education